2011
DOI: 10.1371/journal.pone.0021936
|View full text |Cite
|
Sign up to set email alerts
|

Modified Habitats Influence Kelp Epibiota via Direct and Indirect Effects

Abstract: Addition of man-made structures alters abiotic and biotic characteristics of natural habitats, which can influence abundances of biota directly and/or indirectly, by altering the ecology of competitors or predators. Marine epibiota in modified habitats were used to test hypotheses to distinguish between direct and indirect processes. In Sydney Harbour, kelps on pier-pilings supported greater covers of bryozoans, particularly of the non-indigenous species Membranipora membranacea, than found on natural reefs. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Several physical and biological properties of pilings may explain differences between habitats in recruitment of bryozoans to kelps (see Introduction). Of the factors shown to affect bryo zoans on kelps in this system (Marzinelli et al 2011), shade is likely to affect settlement of larvae because they often respond to reduced amounts of light (Thorson 1964, Rodriguez et al 1993. For example, experimental shading of primary substra- Table 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several physical and biological properties of pilings may explain differences between habitats in recruitment of bryozoans to kelps (see Introduction). Of the factors shown to affect bryo zoans on kelps in this system (Marzinelli et al 2011), shade is likely to affect settlement of larvae because they often respond to reduced amounts of light (Thorson 1964, Rodriguez et al 1993. For example, experimental shading of primary substra- Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, greater densities of sea urchins may reduce settlement of larvae in reefs by enfolding the fronds for attachment or increase post-settlement mor tality by grazing on the kelps (Wahl & Hay 1995). Reducing the shade caused by piers and transplanting urchins to pilings may thus minimize the changes in biodiversity caused by pilings (Marzinelli et al 2011). Patterns of biodiversity are generated and maintained by dynamic ecological processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between fouling organisms such as grazer abundance and predation can in turn affect the abundance and distribution of other fouling organisms. Marzinelli et al (2011) modelled the presence of artificial habitats such as pilings on sea urchin abundance and found that a decrease in the abundance of sea urchins caused an increase in the cover of fouling bryozoans on kelp. In addition, competition between species can have an effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the mechanisms of combined environmental stressors in order to predict an organism's responses to future climate scenarios. Experimental transplants can provide a better understanding of such effects (Marzinelli et al 2009(Marzinelli et al , 2011.…”
Section: Introductionmentioning
confidence: 99%